The Post Cold War World - Cox, Michael , author.
1 online resource (272 pages)
Keywords: This book by a leading scholar of international relations examines the origins of the new world disorder– the resurgence of Russia, the rise of populism in the West, deep tensions in the Atlantic alliance, and the new strategic partnership between China and Russia– and asks why so many assumptions about how the world might look after the Cold War – liberal, democratic and increasingly global– have proven to be so wrong. To explain this, Michael Cox goes back to the moment of disintegration and examines what the Cold War was about, why the Cold War ended, why the experts failed to predict it, and how different writers and policy-makers (and not just western ones) have viewed the tumultuous period between 1989 when the liberal order seemed on top of the world through to the current period when confidence in the western project seems to have disappeared almost completely.